Evolution of the mandibular appendage in fig wasps (Hymenoptera: Agaonidae) - Ramírez B., William (1991)
The phylogenetic value of the conformation of the mandibular appendages, the number of mandibular glands and other head characters in the Agaonidae are examined. The phylogenetic arrangement suggests that the preagaonid had a normal bidentate mandible with two glands, and a undistinct facial groove as in sorne Diaziella (Sycoecinae), Sycophaga (Sycophaginae) and in related chalcidoid non-pollinating fig wasps. lt also had thirteen-segmented antennae;' a long scape, several times ¡onger than wide a long triangular pedicel, two or three anelli and eight flagellomeres with sensilla (as uniquely found in Tetrapus). The mandibular appendage apparently co-evolved with the development oí the ostiolum of the syconium and the first mandibular appendage was fixed and had ridges or lameUae. A flexible hinge evolved later at its base. The polygamous males were wingless with extendible (solenogastrus) abdomen and mate inside the galls. These characters are also found in most Sycophaginae. The ancestor of Aganoidae was probably a primary sycophilous wasp, with dorsoventral depressed head, thorax and abdomen, that oviposit through the stylar channel as stiU Sycophaga sycomori does. Sycophaga wasps with its apterous and polygamous males seem to be the sister group of Agaonidae. The Agaonidae females are characterized by their mandibular appendage and the antennal process. They have a prognathous head with gula. The males are wingless polygamous and solenogastrous